Desigualdade de transplantes de òrg\~aos no Brasil: Análise do perfil dos receptores por sexo e raça ou cor - Alexandre Marinho; Simone de Souza Cardoso; Vivian Vicente de Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– According to Brazilian Law, access to organ transplantation in Brazil should be equitable for all and not be influenced by race, geography, religion, or economic status. But we show that non-Whites and women are underrepresented among organ transplantation recipients, although they are no longer minorities in Brazil. The problem is reinforced, since there are not marked differences in the needs of organ transplantation against these groups. These inequalities may result from a number of factors.
Keywords: I14; I18; J15; J16; 330